Transmedia Storytelling and CLIL approach: the perfect allies in the English Language classroom - Heit, Graciela (2023)
During the last two decades the concept of a post- method for teaching foreign languages gained wide acknowledgement in the educational arena. This approach also known as CLIL ( Content and Language Integrated Learning) aims at articulating students‘ general curricula with the teaching of the foreign language. Similarly, transmedia literacy also proposes a new form of learning in which students are expected to expand the content of their studies by means of different platforms in a more engaging and cooperative way. It seems to be that both concepts of CLIL and Transmedia Storytelling can interweave towards the same objective, one becoming the support of the other. This article presents a brief theoretical framework, and the implementation, results and future implications of an educational project. Such experience was performed with two different groups: one with a third form students from a secondary school in their English class, and another one with students who are attending Geography as part of their educational programme from the Teacher Training course (TTC) of English from UNAHUR. The project pivoted around the topics of the exploitation of Natural Resources and the environmental impact it may cause by means of the use of different media platforms.